To solve this equation, cross multiply to eliminate the fractions:
(x + 3)(x + 3) = 3 * 7
(x^2 + 6x + 9) = 21
x^2 + 6x - 12 = 0
Now we have a quadratic equation. We can solve it by factoring:
(x + 3)(x - 2) = 0
Setting each factor to zero gives us:
x + 3 = 0 or x - 2 = 0
x = -3 x = 2
Therefore, the values of x are -3 and 2.
Solve for all values of x.
x, plus, start fraction, 3, divided by, x, plus, 3, end fraction, equals, start fraction, 7, divided by, x, plus, 3, end fraction
x+
x+3
3
=
x+3
7
7 answers
answer resalt in division by zero should be excluded
Apologies for the oversight. Let's exclude the value that makes the denominator become zero when solving for x:
x + 3 ≠ 0
x ≠ -3
Therefore, the only valid solution is x = 2.
x + 3 ≠ 0
x ≠ -3
Therefore, the only valid solution is x = 2.
are you sure
Let's re-evaluate the solution to ensure accuracy:
Given equation:
(x + 3)/(x + 3) = 7/(x + 3)
Since the left side of the equation simplifies to 1 for any value of x (unless x = -3, which is not included in the domain), we can simplify the equation to:
1 = 7/(x + 3)
Now, solving for x gives:
x + 3 = 7
x = 7 - 3
x = 4
Therefore, the only valid solution for x is x = 4.
Given equation:
(x + 3)/(x + 3) = 7/(x + 3)
Since the left side of the equation simplifies to 1 for any value of x (unless x = -3, which is not included in the domain), we can simplify the equation to:
1 = 7/(x + 3)
Now, solving for x gives:
x + 3 = 7
x = 7 - 3
x = 4
Therefore, the only valid solution for x is x = 4.
Solve for all values of x.
x, minus, start fraction, 1, divided by, x, minus, 1, end fraction, equals, start fraction, 5, divided by, x, minus, 1, end fraction
x−
x−1
1
=
x−1
5
x, minus, start fraction, 1, divided by, x, minus, 1, end fraction, equals, start fraction, 5, divided by, x, minus, 1, end fraction
x−
x−1
1
=
x−1
5
To solve this equation, we will cross multiply to eliminate the fractions:
x(x - 1) = 1 * 5
x^2 - x = 5
x^2 - x - 5 = 0
Now, let's solve this quadratic equation using the quadratic formula:
x = (-(-1) ± sqrt((-1)^2 - 4*1*(-5))) / 2*1
x = (1 ± sqrt(1 + 20)) / 2
x = (1 ± sqrt(21)) / 2
Therefore, the solutions for x are:
x = (1 + sqrt(21)) / 2
x = (1 - sqrt(21)) / 2
x(x - 1) = 1 * 5
x^2 - x = 5
x^2 - x - 5 = 0
Now, let's solve this quadratic equation using the quadratic formula:
x = (-(-1) ± sqrt((-1)^2 - 4*1*(-5))) / 2*1
x = (1 ± sqrt(1 + 20)) / 2
x = (1 ± sqrt(21)) / 2
Therefore, the solutions for x are:
x = (1 + sqrt(21)) / 2
x = (1 - sqrt(21)) / 2